Advanced functional polymers for biomedical applications - Mozafari, Masoud; Chauhan, Naren Pal Singh (Elsevier, 2019)
Advanced Functional Polymers for Biomedical Applications presents novel techniques for the preparation and characterization of functionalized polymers, enabling researchers, scientists and engineers to understand and utilize their enhanced functionality in a range of cutting-edge biomedical applications.